Importance of displacements of the duodenum and the colon, for the topographic diagnosis of abdominal tumors: (The importance of methodizing the radiological study) - García Capurro, F.; Predari, F. N. (Cirugía del Uruguay, 2020)
Presented at the session of June 25th, 1941.